(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Nanomaterials having at least one exterior dimension of 1 to 100 nanometers are classed as materials. Nanomaterials may arise or develop naturally or be manufactured to perform a particular function as by-products of combustion processes. The physical and chemical characteristics of these materials may differ from the counterparts of their bulk form. As a consequence of recent technical developments, nanomaterials of different sizes and forms were produced. These discoveries will serve as a basis for future engineering to develop new characteristics suited to specific applications. Nanomaterials have been utilized in a number of previous sectors, including food production, environmental research and medical, in an effective and secure manner. In the scientific community, however, the application in agriculture is under-explored, especially in plant conservation and processing. Nanomaterials are, according to early study, capable of improving plant safety, germination and development in seeds, identification of pathogens and detection of pesticide/herbicide residues. This research covers the agricultural uses of nanomaterials and their pros